MENGUKUR KINERJA ADMINISTRASI KARYAWAN DIVISI PLANT, AKUNTING DAN FINANCE, SERTA MARKETING PADA PT X, JAWA BARAT DENGAN MODEL PENDEKATAN INTERNAL BENCHMARKING - Budi Satria; Achiruddin Achiruddin (JABE (Journal of Applied Business and Economic), 2015)
This study wanted to reveal  that human resources is a source of competitive advantage and the key elements that are important for success in competing to achieve the goal. Therefore, the management of human resources for the organizations that are important to the public service. Human resources are part of management. Which is an element of management in which there are workers in the company. Humans are always active and dominant in every activity of the organization, because people become planners, perpetrators and determines the realization of organizational goals. The method used is a survey method, the research took samples from a population and using questionnaires as the primary means of collecting data. Variables to be explained is the performance division of plant administration employees; accounting and finance; and marketing at PT. X, West Java with a model of  internal benchmarking approach. Based on the research results can be seen that; 1) formal education possessed by employees is still low enough to need a special program to increase pendididkan formal, 2) Evenness skills are needed so that each division can  be run optimally and can cooperate well, so the company needs to increase training for employees, 3 ) on Marketing Division achievement of the goals pretty good / high, one faktonya is because the payroll system at the Division markeing that inevitably mentimulasi employees to achieve the target that has been determined. So in this regard, it is necessary to go back and reexamined managed payroll system more effective in order to improve the performance and productivity of employees.